Structural performance of large-scale concrete beams reinforced with cementitious composite containing different fibers. (June 2021) - Ismail, Mohamed K.; Hassan, Assem A.A.
Abstract: This study investigated the structural behavior of large-scale normal concrete (NC) beams repaired with different fiber-reinforced cementitious composites (FRCC). To simulate the repair method, a specific layer of the NC beam was replaced by the FRCC in either the tension or compression zone. In this investigation, two types of FRCC were used, namely ECC and SFRCC, which were developed with same mixture composition but different fibers, i.e., polyvinyl alcohol (PVA) fibers in ECC and steel fibers (SFs) in SFRCC. The behavior of the ECC, SFRCC and repaired beams was compared to control beam fully cast with NC. The investigated parameters included load-deflection behavior, cracking and failure mode, first crack and ultimate load, ductility, and energy absorption capacity. The results indicated that the fully cast ECC and SFRCC beams showed a significantly improved flexural performance compared to the fully cast NC beam, especially with SFRCC. Repairing NC beam with ECC or SFRCC at the compression zone obviously contributed to improving the ultimate load, ductility, and energy absorption capacity compared to the fully cast NC beam. These improvements were more pronounced in beam repaired with SFRCC compared to ECC. Meanwhile, repairing the NC beam with ECC or SFRCC at the tension zone contributed to controlling the initiation and propagation of cracks, thus providing better durability performance.